Global Survey of Guidelines for the Management of Epilepsy in Pregnancy: A report from the International League Against Epilepsy Task Force on Women and Pregnancy - Torbjörn Tomson; Dina Battino; Rebecca Bromley; Silvia Kochen; Kimford J. Meador; Page B. Pennell; Sanjeev V. Thomas (Epilepsia Open, 2020)
Abstract The ILAE Task Force on Women and Pregnancy conducted a survey among ILAE Chapters of their use of guidelines or recommendations for the management of women with epilepsy during pregnancy. A web‐based questionnaire including 10 questions was sent to the 118 ILAE Chapters in December 2017 with repeated reminders until the end of February 2018. In total, 77 chapters (65%) responded, although not to all questions. Out of those responding, 68% reported having guidelines or recommendations, 34% of which were from 2014 or earlier. At least 20% of the guidelines did not include information on possible risk to cognitive development, information regarding specific risks with specific antiepileptic drugs, nor recommendations regarding selection of antiepileptic drugs. Among those responding to the question, 91% reported that recommendations were made regarding folate supplementation, but the recommended dose ranged from 0.4 mg/d to 4 mg/d or more; 34% did not include recommendations regarding drug level monitoring during pregnancy, and 19% did not include guidelines on breastfeeding. Our survey demonstrates that there is a need for the development of up‐to‐date, globally applicable recommendations for the management of epilepsy during pregnancy.